Segmental Osteotomy with Interpositional Graft in Posterior Maxilla Area (International Journal of Medical and Surgical Sciences, 2014)
A variety of techniques have been documented for the recovery of bone loss in areas where rehabilitation with dental implants is planned. The loss of teeth is followed by the loss of height and thickness of the bone too, precluding the installation of dental implants. The premature bone loss in this region can also cause pneumatization of the maxillary sinuses. So, the corrections of these defects are a real challenge for dentists and oral surgeons. The technique of segmental osteotomy with bone interposition graft has proven to be a viable option to solve this problem. This clinical case report describes the successful application of the technique in the treatment of decreased vertical dimension in the posterior area of the maxilla, where 7 months later 4 dental implants were installed. Two dental implants of 13 mm, and two dental implants of 11 mm, demonstrating success with bone height that was achieved in the case, making the use of this technique very sustainable in bone loss of posterior area of the maxilla with pneumatized maxillary sinuses.